The Impact of Using the Bamboozle Platform on Preschoolers’ Recognition of CVC Words: A Qualitative Study - Qurrata'ain; Luthfi Awwalia (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2026)
Early exposure to consonant-vowel-consonant (CVC) word patterns plays an important role in developing preschoolers’ phonemic awareness and reading skills. Using interactive platforms such as Bamboozle can support and engage learners in learning CVC words. This study explores the impact of using Bamboozle on preschoolers’ recognition of CVC word patterns. A qualitative study was conducted involving 10 preschool students and 4 teachers at Smart and Shine Child Development and Learning Centre. Data were collected through classroom observation, interviews, and field notes, and analyzed using thematic analysis. The findings indicate that Bamboozle promotes learners’ engagement, supports CVC word recognition, and enhances phonemic activities through interactive and multimodal learning activities. Bamboozle also supports visual and auditory features that help in recognizing and distinguishing CVC word patterns. The study suggests that integrating game-based digital platforms can support early literacy development in an early childhood English class. However, the findings should be interpreted cautiously due to the small sample size and the qualitative nature of the study, which focuses on descriptive insights rather than generalizable outcomes. Future research may involve larger samples and mixed-method approaches to further examine the effectiveness of digital platforms in early literacy instruction.